UJI EFEKTIVITAS ANTIFUNGI EKSTRAK KULIT BIJIKAKAO (Theobroma cacao, L.) TERHADAP PERTUMBUHAN Trichophyton rubrum SECARA IN VITRO - Chintya Mei Desia Hutasoit, (2020)
Dermatophytosis is a fungal infection caused by dermatophytes, with the most common cause is Tricophyton rubrum. Antifungal agent have several problems such as fungal resistance and side effects of therapy. The result of phytochemical test of cacao bean shells extract (Theobroma cacao L.) contained alkaloids, saponins and flavonoids which have antifungal effect. The aim of this study is to test the effectiveness of antifungal cacao bean shells extract to Tricophyton rubrum growth in vitro by agar well difussion method. The experimental method was used in this research with post test only control group design using cacao bean shells extract concentration 25%, 50%, 75%, and 100%, Ketokonazol as control positive, and aquades as control negative. Cacao bean shells extract concentration 25%, 50%, 75%, and 100% produced an average inhibitory diameter of 10,65 mm, 18mm, 26,92 mm, and 37,22 mm respectivity and Ketokonazol 51,52 mm. There are significant differences between each treatment group, p = 0,003. Cacao bean shells extract (Theobroma cacao L.) has antifungal effectiveness in inhibiting the growth of Tricophyton rubrum in vitro by agar well difussion method